Analisis Manajemen Sumber Daya Manusia: Keterkaitan Rekrutmen, Analisis Jabatan, Penilaian Kinerja, dan Kompensasi Karyawan - Cut Zaara Nazwa Shafina; Marzuti Isra; Suhenri Suhenri; Purjianto Purjianto; Ariga Kus Arindra; Farhan Wahyudi; Adi Prana Jaya; Ariq Ahmad Fauzan; Jaksa Fahrezi Siregar (Jurnal Inovasi Manajemen, Kewirausahaan, Bisnis dan Digital, 2026)
Human resource management plays a strategic role in supporting the achievement of organizational goals through integrated and sustainable workforce management. This study aims to analyze the relationship between recruitment, job analysis, performance appraisal, and employee compensation as an integrated system in human resource management. The research approach used is a literature study by reviewing various scientific literature, textbooks, and previous research results relevant to the topic of human resource management. The results of the analysis show that an effective recruitment process is highly dependent on the clarity of job analysis, which includes job descriptions and specifications as the basis for appropriate workforce placement. Furthermore, performance appraisal serves as an evaluation tool to measure the achievement of employee work analysis based on standards set in the position. The research findings also reveal that a fair and competitive improvement system is closely related to performance appraisal results, thereby increasing motivation, job satisfaction, and overall employee performance. Thus, the integration of recruitment, job analysis, performance appraisal, and employee compensation is a key factor in creating effective and competitive human resource management. This study is expected to contribute academically and serve as a practical reference for organizations in designing and implementing human resource management policies.